Duration of extracorporeal life support bridging delineates differences in the outcome between awake and sedated bridge-to-transplant patients. (2nd August 2022) - Ponholzer, Florian; Schwarz, Stefan; Jaksch, Peter; Benazzo, Alberto; Kifjak, Daria; Hoetzenecker, Konrad; Schweiger, Thomas
Abstract: OBJECTIVES: Traditionally, patients on bridge-to-transplant extracorporeal membrane oxygenation were kept sedated and intubated. However, awake bridging strategies have evolved during recent years. This study aims to elaborate differences in physical activity and postoperative outcomes after lung transplantation (LTx), depending on bridging strategy and duration. METHODS: Bridged patients receiving LTx between March 2013 and April 2021 were analysed. Awake bridging was defined as a Richmond Agitation-Sedation Scale score of ≥−1 until 24 h before transplantation. Patients were grouped in awake and sedated cohorts. RESULTS: A total of 88 patients (35 awake, 53 sedated bridging) were included. After LTx, mobilization to standing position was achieved earlier in awake bridged patients (7 vs 15 days, P < 0.001). Postoperative ventilation time (247 vs 88 h, P  = 0.005) and intensive care unit stay (30 vs 16 days, P  = 0.004) were longer in the sedated cohort. Awake patients with bridging duration >6 days showed shorter postoperative ventilation time (108 vs 383 h, P  = 0.003), less intensive care unit days (23 vs 36, P  = 0.003) and earlier mobilization to standing position (9 vs 17 days, P < 0.001). In contrast, postoperative ventilation time and days in intensive care unit in patients with bridge-to-transplant duration ≤6 days were comparable between cohorts. Mobilization to standing position was achieved faster in the awake (≤6 days) bridged cohort (5 vs 9 days, P  = 0.024). CONCLUSIONS: Despite the complex management of bridged patients, excellent survival rates after LTx can be achieved. Especially in patients with more than 1 week on extracorporeal membrane oxygenation, awake bridging concepts are associated with significantly faster recovery. Abstract : Lung transplantation (LTx) has evolved to be a routinely performed procedure in selected patients with end-stage lung disease.